Structural Roles for the Juxtamembrane Linker Region and Transmembrane Region of Synaptobrevin 2 in Membrane Fusion - Hu, Yaru; Zhu, Le; Ma, Cong (Frontiers in Cell and Developmental Biology, 2021)
Formation of the trans-SNARE complex is believed to generate a force transfer to the membranes to promote membrane fusion, but the underlying mechanism remains elusive. In this study, we show that helix-breaking and/or length-increasing insertions in the juxtamembrane linker region of synaptobrevin-2 exert diverse effects on liposome fusion, in a manner dependent on the insertion position relative to the two conserved tryptophan residues (W89/W90). Helical extension of synaptobrevin-2 to W89/W90 is a prerequisite for initiating membrane merger. The transmembrane region of synaptobrevin-2 enables proper localization of W89/W90 at the membrane interface to gate force transfer. Besides, our data indicate that the SNARE regulatory components Munc18-1 and Munc13-1 impose liposome fusion strong demand on tight coupling between the SNARE motif and the transmembrane region of synaptobrevin-2.